1984
DOI: 10.1149/1.2115678
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Passivity of Nickel by Fluoride: II . Surface Analytical Studies

Abstract: Passive layers on nickel and their change by the action of fluoride have been studied by surface analyses such as x‐ray photoelectron spectroscopy (XPS) and low energy ion scattering (ISS). The thickness of the layers is deduced from the height of the XPS signals normalNi2normalp3/2 , O1s, and F1s and their attenuation by covering layers. Argon sputtering gives information on the in‐depth structure of the passivating films in combination with XPS and the higher depth resolution of ISS. Their thickness and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 1 publication
8
45
1
Order By: Relevance
“…This model is supported by X-ray photoelectron spectroscopy (XPS) investigations. 1 -5 The XPS data reveal two fairly well resolved O 1s peaks at 529.8 eV and 531.6 eV, and these two peaks correspond well to the positions of oxygen in NiO and Ni(OH) 2 . 1 However, these spectral features may also be interpreted differently since Ni 3C can give rise to spectral features very similar to those of Ni(OH) 2 .…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…This model is supported by X-ray photoelectron spectroscopy (XPS) investigations. 1 -5 The XPS data reveal two fairly well resolved O 1s peaks at 529.8 eV and 531.6 eV, and these two peaks correspond well to the positions of oxygen in NiO and Ni(OH) 2 . 1 However, these spectral features may also be interpreted differently since Ni 3C can give rise to spectral features very similar to those of Ni(OH) 2 .…”
Section: Introductionmentioning
confidence: 79%
“…9 In addition, the structure of the inner oxide layer did not vary with the time or potential of passivation. 9 A nearly saturated layer of hydroxyl groups with a 1 ð 1 epitaxy can be formed on NiO(111), and further exposure to water leads to the formation of a nearly complete monolayer of nickel hydroxide similar to that found inˇ-Ni(OH) 2 . 12 Further investigation of this bilayer structure indicated that hydroxylation of the NiO thin film on Ni(111) was structurally sensitive.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations